CLINICAL CHARACTERISTICS OF CHILDREN UNDER INVESTIGATION FOR DENTAL CARIES AMONG CHILDREN (World Bulletin of Public Health, 2024)
In modern dentistry, despite the use of various methods of prevention and treatment of dental hard tissue caries, it remains one of the most common diseases of dental hard tissue. There are hundreds of reasons that contribute to the development of caries in milk teeth. The most important of them are socio-demographic, biological, dietary, hygienic and nutritional factors. In this case, the occurrence or attenuation of a number of conditions will later determine the early development of caries in children.
Keywords: caries disease; dental hard tissues; dental care